Angular momentum and orientation effects in excitation-ionization collisions. (5th August 2016) - Harris, A L; Esposito, T P
Abstract: We present theoretical fully differential cross sections (FDCS) for electron-impact excitation-ionization of helium in which the final state He + ion is oriented in a particular direction. Specifically, we study the process for He + ions in the 2p0 state. Using our 4-body distorted wave model, we show a strong dependence of the FDCS on the ion's orientation and trace some unexpected structures in the FDCS to the L  = 2 term in the partial wave expansion for the ionized electron. A comparison is drawn to the ionization of oriented Mg (3p0) atoms, and unlike that process, we find that for excitation-ionization angular momentum must be transferred from either the projectile or the target atom.